Endoscopic sleeve gastroplasty versus intragastric balloon insertion: efficacy, durability, and safety - Fayad, Lea; Cheskin, Lawrence J.; Adam, Atif; Badurdeen, Dilhana S.; Hill, Christine; Agnihotri, Abhishek; Dunlap, Margo; Simsek, Cem; Khashab, Mouen A.; Kalloo, Anthony N.; Kumbhari, Vivek (Endoscopy, 2019)
Background Intragastric balloon (IGB) placement and endoscopic sleeve gastroplasty (ESG) are reported to be safe and effective endoscopic bariatric therapies. This study aimed to compare the patient demographics and therapeutic outcomes between the IGB and ESG procedures.Methods: This was a retrospective review of prospectively collected data from consecutive patients between December 2015 and October 2017 who underwent IGB or ESG at a single academic center. Fluid-filled IGBs implanted for a 6-month duration were used. IGB and ESG patients were subjected to identical post-procedure dietary instructions and follow-up protocols. Body weight was recorded at 1, 3, 6, and 12 months post-procedure. Results A total of 47 patients underwent IGB insertion and 58 underwent ESG. The IGB cohort had a lower baseline body mass index (BMI) than the ESG (34.5 vs. 41.5 kg/m2; P < 0.001) and a significantly lower proportion of men (2.1 % vs. 41.4 %; P < 0.001). IGB patients showed a mean (standard deviation [SD]) percentage total body weight loss (%TBWL) that was significantly lower than ESG patients at 1 month (6.6 % [2.6 %] vs. 9.9 % [2.4 %]; P < 0.001), 3 months (11.1 % [4.4 %] vs. 14.3 % [4.6 %]; P = 0.004), 6 months (15.0 % [7.6 %] vs. 19.5 % [5.7 %]; P = 0.01), and 12 months (13.9 % [9.0 %] vs. 21.3 % [6.6 %]; P = 0.005). The IGB cohort also experienced significantly more adverse events compared with the ESG (17 % vs. 5.2 %; P = 0.048). Conclusions IGB placement and ESG result in clinically meaningful weight loss. However, ESG appears to provide clinically superior and more enduring weight loss with fewer adverse events compared with an IGB.